Wimba learning strategy with PjBL model: How the effect student in excretory system concept? - Suprapto, Purwati Kuswarini; Aji Riyanto; Nuryadin, Egi (Biosfer: Jurnal Pendidikan Biologi, 2020)
This research aims to determine the effect of wimba learning strategies with project based learning models toward student learning outcomes on the excretory system material. This research was conducted in September 2018 until September 2019. The research method used a true experiment with a population of all class XI in one of the State High School of Tasikmalaya City with 8 classes with a total of 288 students. The samples used were 2 classes taken by cluster random sampling, namely class XI mathematics and science 1 as a controller class and class XI mathematics and science 4 as an experimental class. Based on the results of the study, data analysis using the Ancova test and hypothesis testing can be concluded that there is an influence of the wimba learning strategy with project based learning model toward student learning outcomes on the excretory system material in class XI in one of the State High School of Tasikmalaya City 2018/2019.